Membentuk Kepribadian Muslim Peserta Didik Melalui Pendidikan Berbasis Akhlak - Wismanto Wismanto; M.Ramadhan Saputra; Tania Aulia Sabila; Amrullah Luqmanul Hakim; Ihsan Priatama Sukma (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to (1) determine the moral education program in forming the Muslim personality of students (2) determine the implementation of moral education in forming the Muslim personality of students (3) identify factors that support and limit the process of forming a Muslim personality. This research uses a qualitative approach. Research data was collected through observation, interviews and document analysis. The research results show that: (1) Moral education programs are generally divided into two activities, namely intracurricular and extracurricular. (2) The implementation of moral education through moral education programs in activities inside and outside the school is carried out in the form of programs and activities which are divided into 4 types: programs, daily activities, weekly and monthly activities and annual activities. (3) Factors that support the implementation of moral education to shape students' Islamic character, namely motivation, physical facilities, facilities and the role of the school principal. In this case, to optimize the results of moral education programs in shaping the character of Muslim students, there must be good cooperation and accountability between institutions, school principals, and teachers, students, facilities and supporting facilities. The factor that hinders the implementation of moral education to shape students' personalities is the lack of student awareness.